Implementasi Multiakad Dalam Fatwa Dewan Syariah Nasional (DSN-MUI) Tentang Pasar Uang - Sari, Nurita; Mustofa, Mustofa (Program Studi Perbankan Syariah Institut Al-Fithrah (IAF) Surabaya, 2024)
This research discusses the implementation of multi-contract in the fatwa of the National Sharia Council of the Indonesian Ulema Council (DSN-MUI) related to the money market. Multi-contract is a combination of several contracts in one transaction that aims to fulfill complex needs in modern economic activities. In the context of the money market, multi-conduct can include a combination of contracts such as mudharabah, musyarakah, murabahah, and ijarah. This research examines the extent to which the DSN-MUI fatwa accommodates the application of multi-conduct in money market products, as well as legal analysis and its application in Islamic banking practices in Indonesia. The research method used is a literature study with a qualitative approach to understand the sharia principles underlying the fatwa. The results show that the implementation of multi-cad in the DSN-MUI fatwa allows flexibility and innovation in the development of Islamic money market products, although it must still pay attention to the principle of prudence and synergistic efforts are needed between regulators, Islamic financial institutions, and academics to overcome these challenges. Concrete steps such as unifying interpretations, strengthening cooperation, clear operational standards, and active involvement of industry players are expected to ensure the development of the Islamic money market in line with the desired sharia principles.